Comparative analysis of the metabolites and biotransformation pathways of fentanyl in the liver and brain of zebrafish - Liu, Meng; Huang, Jian; Zhao, Sen; Wang, Bin-jie; Zhou, Hong; Liu, Yao (Frontiers in Pharmacology, 2023)
The rise of fentanyl has introduced significant new challenges to public health. To improve the examination and identification of biological samples in cases of fentanyl misuse and fatalities, this study utilized a zebrafish animal model to conduct a comparative investigation of the metabolites and biotransformation pathways of fentanyl in the zebrafish's liver and brain. A total of 17 fentanyl metabolites were identified in the positive ion mode using ultra-high-pressure liquid chromatography Q Exactive HF Hybrid Quadrupole-Orbitrap mass spectrometry (UHPLC-QE HF MS). Specifically, the zebrafish's liver revealed 16 fentanyl metabolites, including 6 phase I metabolites and 10 phase II metabolites. Conversely, the zebrafish's brain presented fewer metabolites, with only 8 detected, comprising 6 phase I metabolites and 2 phase II metabolites. Notably, M'4, a metabolite of dihydroxylation, was found exclusively in the brain, not in the liver. Through our research, we have identified two specific metabolites, M9-a (monohydroxylation followed by glucuronidation) and M3c (monohydroxylation, precursor of M9-a), as potential markers of fentanyl toxicity within the liver. Furthermore, we propose that the metabolites M1 (normetabolite) and M3-b (monohydroxylation) may serve as indicators of fentanyl metabolism within the brain. These findings suggest potential strategies for extending the detection window and enhancing the efficiency of fentanyl detection, and provide valuable insights that can be referenced in metabolic studies of other new psychoactive substances.